Nathaniel Hawthorne: life and works - Olson, Hilda S. (My University, 1897)
Introduction: The head of the American branch of the Hawthorne family, Ww. Hathorne of Wilton, Wiltshire, England, emigrated with Winthrope and arrived at Salem Bay, Mass. June 12, 1630. Nathaniel Hawthorne was born in Salem, Mass. July 4th, 1804. His immediate ancestors were seafaring men, trading with the East Indies. A more remote progenitor was a judge and had been concerned in the trials of the witches in the 17th Century. Others had commanded troops against the Indians. The race had the characteristics of Puritans and were held to be even more stern and conciliating than the average Puritan. The mother of Nathaniel Hawthorne was a woman of beauty, dignity, and unusual intellect. Nathaniel was left fatherless at the age of four. His education was under the superintendence of his maternal uncle, but he was not an assiduous student. He liked desultory reading and out-door play, hunting and skating. He was very fond of taking long walks alone and he often declared to his mother that he would sometime go to sea and never return. He had an arch love for mischief, a consciousness of power and a healthy independence of character. While a child he read Shakespeare, Milton, Pope and Thomson, the Castle of Indolence being an especial favorite.
Citation: Olson, Hilda S. Nathaniel Hawthorne: life and works. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: English; Nathaniel Hawthorne; Theses; Manuscripts (documents)